PENDAMPINGAN WIRAUSAHAWAN MENUJU UMKM BANGKIT KEMBALI PASCA PANDEMI DI YOGYAKARTA - Jana, Padrul; Danuri, Danuri; Indriati, Inayat Hanum; Asriyanti, Isma (Universitas Kadiri, 2023)
The Covid-19 pandemic has not only had an impact on health problems, but has penetrated the economic and business sectors. One of those affected by this outbreak is UKM